Met/HGFR triggers detrimental reactive microglia in TBI - Rehman, Rida; Miller, Michael; Krishnamurthy, Sruthi Sankari; Kjell, Jacob; Elsayed, Lobna; Hauck, Stefanie M.; olde Heuvel, Florian; Conquest, Alison; Chandrasekar, Akila; Ludolph, Albert; Boeckers, Tobias; Mulaw, Medhanie A.; et al. (Cell reports (Cambridge), 2022)
The complexity of signaling events and cellular responses unfolding in neuronal, glial, and immune cells upon traumatic brain injury (TBI) constitutes an obstacle in elucidating pathophysiological links and targets for intervention. We use array phosphoproteomics in a murine mild blunt TBI to reconstruct the temporal dynamics of tyrosine-kinase signaling in TBI and then scrutinize the large-scale effects of perturbation of Met/HGFR, VEGFR1, and Btk signaling by small molecules. We show Met/HGFR as a selective modifier of early microglial response and that Met/HGFR blockade prevents the induction of microglial inflammatory mediators, of reactive microglia morphology, and TBI-associated responses in neurons and vasculature. Both acute and prolonged Met/HGFR inhibition ameliorate neuronal survival and motor recovery. Early elevation of HGF itself in the cerebrospinal fluid of TBI patients suggests that this mechanism has translational value in human subjects. Our findings identify Met/HGFR as a modulator of early neuroinflammation in TBI with promising translational potential. [Display omitted] •TBI is associated with complex, time-dependent patterns of RTK activation•Met is activated in microglia upon TBI, and Met inhibition decreases microglia reaction•Blockade of Met reduces acute and sub-acute motor impairment due to TBI•The Met inhibitor reduces synaptic and neuronal loss after TBI Controlling neuroinflammation in neurotrauma is an important but unachieved goal. Rehman et al. exploit a moderate TBI model and array-based proteomics to identify Met/HGFR as an inducer of reactive microglia. A small-molecule inhibitor of Met/HGFR suppresses microglial reactivity, reduces neuronal and vascular alterations, limits behavioral disturbances, and accelerates recovery.